A typology of European farmers' viewpoints on soil management and an investigation of their context-dependency - Heidi Leonhardt; Michael Braito; Nicole Bütikofer; Morten Graversgaard; Marion Hacek; Jenny Höckert; Ernesto Lunar-Koch; Christina Lundström; Mariella Schreiber; Mette Tiselius (Ecological Economics, 2026)

Unlocking agroforestry: how Danish farmers and landowners perceive trees in agriculture - Niels Mark Jacobsen; Peter Brinkmann Kristensen; Martin H. Thorsøe; Morten Graversgaard; Tommy Dalgaard; Tiffanie F. Stone (Agroforestry Systems, 2026)

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Carbon farming: The foundation for carbon farming schemes – lessons learned from 160 European schemes - Martin Hvarregaard Thorsøe; Ennio Facq; Irene Criscuoli; Laura B. Martínez-García; Claudia Heidecke; Leonardo Amthauer Gallardo; Andrea Martelli; Nikolas Hagemann; Bert Smit; Jennie van der Kolk; Francesco Galioto; Stephane de Cara; et al. (Land Use Policy, 2025)

Unveiling the frontiers: Historical expansion and modern implications of agricultural land use in Denmark - Nele Lohrum; Signe Normand; Tommy Dalgaard; Morten Graversgaard (Journal of Environmental Management, 2024)

Discordance between farmers and scientists - Perspectives on nitrogen reduction measures in Denmark - Sara V. Iversen; Tommy Dalgaard; Morten Graversgaard (Journal of Environmental Management, 2024)

Navigating the nexus: The role of intermediaries in charting a new frontier of policy integration for agrifood and energy systems transformation - Emilia Noel Ptak; Morten Graversgaard; Tommy Dalgaard (Environmental Science & Policy, 2023)

Promise and performance of agricultural nutrient management policy: Lessons from the Baltic Sea - Martin Hvarregaard Thorsøe; Mikael Skou Andersen; Mark V. Brady; Morten Graversgaard; Emils Kilis; Anders Branth Pedersen; Samuli Pitzén; Helena Valve (Ambio, 2022)
Following decades of international collaboration to restore the Baltic Sea, we provide an assessment of the domestic implementation of measures agreed to limit diffuse agricultural pollution and the patterns of policy instruments applied. Despite the Helsinki Convention being unusually specific in detailing what measures countries should introduce, we find many shortcomings. These are most pronounced in the larger countries (Poland, Germany and Russia), while smaller countries perform better, notably Sweden and Estonia. The patterns of policy instruments applied differ, influenced by domestic politics. The limited use of complementary policy instruments suggests that other priorities overrule full and effective implementation, with engagement mirroring the advantages that a restored Baltic Sea can bring to countries. Using the European Agricultural Fund for Rural Development to support farmers in managing nutrients, particularly advisory services and investments in modern manure management technologies, represents a significant opportunity for reducing agricultural pollution in most countries.

Nitrogen footprints: Regional realities and options to reduce nitrogen loss to the environment - Hideaki Shibata; James N. Galloway; Allison M. Leach; Lia R. Cattaneo; Laura Cattell Noll; Jan Willem Erisman; Baojing Gu; Xia Liang; Kentaro Hayashi; Lin Ma; Tommy Dalgaard; Morten Graversgaard; et al. (Ambio, 2017)